Microorganisms in the Deterioration and Preservation of Cultural Heritage - Joseph, Edith; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2021)
This open access book offers a comprehensive overview of the role and potential of microorganisms in the degradation and preservation of cultural materials (e.g. stone, metals, graphic documents, textiles, paintings, glass, etc.). Microorganisms are a major cause of deterioration in cultural artefacts, both in the case of outdoor monuments and archaeological finds. This book covers the microorganisms involved in biodeterioration and control methods used to reduce their impact on cultural artefacts. Additionally, the reader will learn more about how microorganisms can be used for the preservation and protection of cultural artefacts through bio-based and eco-friendly materials. New avenues for developing methods and materials for the conservation of cultural artefacts are discussed, together with concrete advances in terms of sustainability, effectiveness and toxicity, making the book essential reading for anyone interested in microbiology and the preservation of cultural heritage. .
Part 1: Occurrence of microorganisms in heritage materials -- Chapter 1: Microbial growth and its effects on inorganic heritage materials -- Chapter 2: Microbiota and biochemical processes involved for biodeterioration of cultural heritage and protection -- Chapter 3: Molecular-based techniques for the study of microbial communities in artworks -- Chapter 4: Extreme colonizers and rapid profiteers: the challenging world of microorganisms that attack paper and parchment -- Part 2: Green methods again biodeterioration -- Chapter 5: Novel antibiofilm non-biocide strategies -- Chapter 6: Green mitigation strategy for cultural heritage using bacterial biocides -- Chapter 7: New perspectives against biodeterioration through public lighting -- Part 3: Biocleaning and bio-based conservation methods -- Chapter 8: Bioremoval of graffiti in the context of current biocleaning research -- Chapter 9: Ancient textiles deterioration and restoration: the case of biocleaning of an Egyptian shroud heldin the Torino Museum(3y (B-- Chapter 10: Advanced biocleaning system for historical wall paintings -- Chapter 11: Sustainable restoration through biotechnological processes: a proof of concept -- Chapter 12: The role microorganisms for the removal of nitrates and sulfates on artistic stoneworks -- Chapter 13: Protection and consolidation of stone heritage by bacterial carbonatogenesis -- Chapter 14: Siderophore-removal of iron corrosion products from wood and textiles -- Chapter 15: Bio-based corrosion inhibitors for metal heritage. .s
Keywords: Microbiology; Cultural property; Microbial ecology; Microbial genetics; Enzymology; Industrial microbiology; Microbiology; Cultural Heritage; Microbial Ecology; Microbial Genetics; Enzymology; Industrial Microbiology